Leaf structure and ultrastructure changes induced by heat stress and drought during seed filling in field-grown soybean and their relationship with grain yield - Carrera, Constanza Soledad; Solis, Stella M.; Ferricci, María S.; Vega, Claudia Rosa Cecilia; Galati, Beatriz G.; Ergo, Veronica Vanesa; Andrade, Fernando Hector; Lascano, Hernan Ramiro (Academia Brasileira de Ciências, 2021)
Studies focusing on terminal drought combined with heat impacts on plants of agronomic value remain scarce, and even less under field conditions. The objective of this study was to investigate leaf structural and ultrastructural changes induced by heat stress (HS) and drought stress (DS) during seed filling and their relationship with physiological variables and yield determination. Two soybean cultivars were grown in field conditions. During seed filling four treatments were applied, including a control (without manipulation, at ambient temperature and field capacity), HS (episodes exceeding 32°C for 6 h d-1) during 21-d, DS (20% of field capacity soil water content) during 35-d, and HS×DS. Drought principally reduced leaf area, whereas heat decreased leaf thickness, possible as acclimation strategies, but also irreversible reducing CO2 assimilation sites. Both stresses damaged the outer and inner membranes of chloroplasts, causing swollen chloroplasts and accumulation of plastoglobules, loss of chlorophyll content, and negatively affecting chlorophyll fluorescence. Thus, the performance and integrity of the photosynthetic machinery were reduced. Through a morpho-functional perspective and a holistic multiscale approach, our results provide evidence of photosynthesis impairment and yield drops under stressful conditions which were associated with structural and ultrastructural (particularly at the level of chloroplasts) modifications of leaves.